Etyka solidarnosci - Tischner, Jozef (Krakow : Wydawn. Znak, 1981)
An exploration of the spirit of Solidarnosc which brought about the changes in Poland in 1980.
Keywords: NSZZ "Solidarnosc" (Labor organization); Poland -- Politics and government -- 1980-1989.